2020
DOI: 10.1002/fsn3.1398
|View full text |Cite
|
Sign up to set email alerts
|

Effects of four cooking methods on sensory and taste quality of Portunus trituberculatus

Abstract: The effect of heating medium (with water and steam) and initial temperature of heating medium (cold and boiling) on the taste quality and sensory properties of Portunus trituberculatus was investigated. Nonvolatile taste active components in the meat and gonad of crabs cooked under four different methods were detected and compared. Sensory evaluation and electronic tongue assessment were also conducted. Sensory evaluation and electronic tongue indicated that taste quality was different under four cooking metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Xue & Chen (1991) found that the muscle of Chinese shrimp contained a large number of FAAs, of which Gly had the highest content. Shi et al (2020) found that the main amino acids of Portunus trituberculatus were Gly, Ala, Arg and pro, which is very similar to our study. This showed that the prominent feature of FAAs in crustaceans was the presence of a large amount of Arg, Gly, Pro, followed by Ala and Glu.…”
Section: Analysis Of Faassupporting
confidence: 91%
See 1 more Smart Citation
“…Xue & Chen (1991) found that the muscle of Chinese shrimp contained a large number of FAAs, of which Gly had the highest content. Shi et al (2020) found that the main amino acids of Portunus trituberculatus were Gly, Ala, Arg and pro, which is very similar to our study. This showed that the prominent feature of FAAs in crustaceans was the presence of a large amount of Arg, Gly, Pro, followed by Ala and Glu.…”
Section: Analysis Of Faassupporting
confidence: 91%
“…The bitter FAAs, such as Phe and Tyr, were also detected in Chinese shrimp, but their TAV was much lower than 1. Shi et al (2020) reported that when the content of these bitter FAAs was lower than the taste threshold concentration, the sweet and umami FAAs could be enhanced. For example, in the salt solution of sodium glutamate, 0.5-5 mmol L −1 phesignificantly improved its solubility and umami, and Tyr had a similar effect (Lioe et al, 2004).…”
Section: Analysis Of Faasmentioning
confidence: 99%
“…However, different types of heat treatment in cooking lead to undesirable modifications in food, like reduced nutritional values due to alternations in the components of protein fraction and lipid oxidation (Uran & Gokoglu, 2014). Therefore, the effects of cooking procedures on the quality of the final product are praiseworthy of investigation and interesting (Shi et al., 2020). In this study, different cooking methods were selected because there is great variations in the mechanisms of food heating.…”
Section: Introductionmentioning
confidence: 99%
“…These nitrogen compounds can influence the taste of fish meat directly. For example, Asp, Glu, glycine, and alanine can be recognized as umami and sweet tastes, whereas histidine and lysine (Lys) are classified into bitter taste amino acids 30 . Some amino acids display a synergistic relationship with other sweet and umami amino acids to enhance their taste characteristics, such as phenylalanine (Phe) and tyrosine (Tyr) 9,31 …”
Section: Resultsmentioning
confidence: 99%